Various Stages of Pink Fungus (Upasia salmonicolor) in Java - Ambarwati Harsojo Tjokrosoedarmo (Universitas Gadjah Mada, 1995)
Pink fungus in Java is classified as Upasia salmonicolor (Basidiomycetes: Corticiaceae) and its anamorph is Necator decretus. This fungus is a serious pathogen which attacks many woody plants. The pink fungus in Java exhibits five developmental stages on the surface of the host bark: I. An initial cobweb stage as thin, white, cobweb-like hyphal layer, which creeps over the surface of the bark, during which penetration of the host occurs; II. Pseudonodular stage, as conical white pustules occurring only on lenticels or cracks, and only on shady side of branches; III. Teleomorph, occurs as pink incrustation and pink pustules on shady side of branches; IV. Nodular stages, as globose white pustules occurring chiefly on intact bark, but also on the lenticels or cracks, on exposed side of branches; V. Anamorph, as small orange-red sporodochium, on exposed side of branches.